Groma: Documenting Archaeology
Groma is an open access peer-reviewed e-journal focusing on the different methodologies applied to archaeology. Since 2023, it is rated as an A-class journal for Archaeology by the Italian National Agency for the Evaluation of the University System. Particular attention is paid to Mediterranean archaeology and to specific methodological aspects such as archaeological documentation and landscape archaeology.